Manajemen Sarana Dan Prasarana Pendidikan di SMK Pusat Keunggulan (Studi Kasus SMK Islam 1 Blitar): (Studi Kasus SMK Islam 1 Blitar) - Zaki, Ahmad Fuad; Isnandar, Isnandar; Alfianto, Imam (BRILIANT: Jurnal Riset dan Konseptual, 2025)
Vocational High Schools (SMK) play a role in producing workers who are ready to compete in the industrial world. To produce high-quality graduates, the availability of adequate facilities and infrastructure is a key supporting factor. SMK Islam 1 Blitar is one of the schools designated as a Center of Excellence (PK) and has the responsibility of producing high-quality graduates. This study aims to describe the management of facilities and infrastructure at SMK Islam 1 Blitar in supporting its role as an SMK PK. The research method used is a qualitative approach with data collection techniques through interviews, participant observation, and documentation. The research findings indicate that the management of facilities and infrastructure at this school is effective through the stages of planning, organizing, implementing, and supervising. These findings are important for studying the management of SMK PKs in efforts to improve the quality of graduates so that they possess competencies aligned with the needs of the workforce and industry.